GROSS MORPHOLOGICAL CHANGES IN PREMATURE AND POST MATURE HUMAN PLANCENTAE - Sherin, Fatima; Afzal, Ejaz; Seema, Nighat (Journal of Ayub Medical College Abbottabad, 2015)
Background: Placenta is a valuable tool for maternal and foetal diseases. Gross pathological changes are seen in the placenta of many disorders of pregnancy, which are associated with high perinatal morbidity and mortality. This study was conducted with the aim to compare the morphological features of preterm, term and post term placentae in our setup. Methods: This cross sectional study was conducted on 150 placentae: 50 were from normal (term) pregnancies considered as control (delivered between 37 to 42 weeks of gestation.), 50 from premature pregnancies (gestational age between 35-37 weeks) from mothers having hypertensive disorders of pregnancy, and 50 from post mature pregnancies (gestational age more than 42 weeks). The placentae were collected from Department of Obstetrics and Gynaecology, Khyber Teaching Hospital, Peshawar, through purposive sampling. Placentae were examined in the department of Anatomy, Khyber Medical College Peshawar. Results: In gross morphological features of placentae (weight and diameter) showed significant (p<0.001) among the groups Conclusion: In was concluded that the hypertensive disorders of the pregnancy adversely influence the morphology of placenta, which leads to the premature delivery. Keywords: Pregnancy, Premature, Postmature, Insufficiency, Placentae, Hypertensive, Gestational age